Análise teórica e experimental do comportamento do gerador síncrono de polos salientes em regime permanente não senoidal - Alves, Manoel Berto (2011)
This study aimed at the identification and treatment of harmonic interference in the functioning of Salient Pole Synchronous Machines in order to make the techno-scientific community aware of such events. Mathematical models, computer simulations, laboratory tests and field measurements were developed as well as the creation and simulation of a new voltage waveform for the machine excitation system, which resulted in attenuation of electromagnetic torque oscillations even though this machine is operating under non-sinusoidal condition. To enable the precision and understanding of the rotating electric machine under non-sinusoidal load currents, the modeling and simulations took into account the harmonic components of the spatial distribution of magnetic flux density produced by machine windings, and the temporal harmonic components produced by non-linear loads. Comparisons were made between sinusoidal and non-sinusoidal steady-state synchronous machine operations, in order to give credibility for the developed mathematical models.